MOTIVASI MAHASISWA MELANJUTKAN PENDIDIKAN PADA PROGRAM MAGISTER SOSIOLOGI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Waruwu, Peresia; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at Pascasrjana Faculty of Social and Political Sciences, University of Riau. Objectives to be achieved in this study are: (a) To know how the motivation of students of Master of Sociology. (b) To find out what are the factors that influence the motivation of students who continue their education in the Sociology Master program. The approach used in this research is quantitative with descriptive quantitative analysis. From the result of the research, it can be concluded that the motivation of students who continue their education in Sociology Master Program of Faculty of Social and Political Sciences of Riau University is the motivation of intrinsic and extrinsic motivation which in intrinsic and extrinsic there are six factor which result from student motivation to continue this Sociology Master Program Is a good category with a score of 3238. While the results of factors that affect the motivation of good categorized is the needs, expectations, interests, family encouragement. While the other two factors that do not contribute in the motivation of students continue the program Master Sociology with the category is not good ie environment and media.Keywords: Motivation, Factor, Education Master Program Sociology